Intelligent university timetable scheduling system using sudoku grid with magic square - Isra Natheer Alkallak; Ruqaya Zedan Shaban; Yazen Hudhaifa Shakir Alnema (Bulletin of Electrical Engineering and Informatics, 2022)
Examination timetabling is problem faced by many academic educational institutions. The situation formulated as artificial intelligence problems as Sudoku grid with Magic square. Problem assigning a set of examinations to a fixed number of examination periods so that no student is required to take more than one examination at a time. The research describes two proposed heuristic algorithms to create university examination timetabling and avoiding the overlapping of exams. We proposed two algorithms, the first algorithm is based on Sudoku grid, a number of hard constraints as well as a number of soft constraints are proposed. We assigned exams as 9 to period as 27 slot times and to 3 rooms, with 3 classes. Each student in each class takes 9 exams While, the second algorithm simulates the classic manual methods while observing the hard and soft constraints of the problem. The heuristic approach used to further optimize the result to include hard constraints with soft. The proposed methodology for creating the Exam timetabling problem has been implemented in Matlab and closing the gap between classical methods and intelligent methods. The results obtained with very less computational effort through two algorithms.